PROBLEMS RELATED TO THE STRUCTURE AND MEANING OF LANGUAGE, SUCH AS HOMOPHONES, HOMONYMS, AND SYNTACTIC AMBIGUITY IN BOTH SPOKEN AND WRITTEN FORMS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Language structure and meaning often present challenges in communication, particularly through issues like homophones, homonyms, and syntactic ambiguity. These linguistic phenomena can cause confusion, misinterpretation, and ambiguity in both spoken and written forms. Homophones and homonyms lead to misunderstandings due to similar sounds or multiple meanings of words, while syntactic ambiguity arises from sentence structure. This paper explores these challenges, examining how they affect comprehension and communication, and suggests methods for reducing their impact in both academic and everyday settings.